PARADIGMA TASAWUF DALAM MEMBANGUN KETAHANAN KELUARGA: ANALISIS KISAH RABI’AH AL-‘ADAWIYAH DALAM SYARH ‘UQUD AL-LUJAYN - Rohma, Dika Purnama Aulia; Putri, Lintang Dewi Fi'liya (ROSYADA: Islamic Guidance and Counseling, 2025)
Family in Islam is a sacred bond founded on compassion, mutual support, and the pursuit of happiness in this world and the hereafter. However, modernity, economic pressures, and digital culture have weakened the spiritual values of the household, creating marital relationships that are increasingly materialistic and lacking inner direction. As a result, harmony declines and divorce rates rise. Revitalizing Sufi values is therefore necessary to restore a family bond oriented toward divine love. This article explores the concepts of love and ukhuwah rūḥaniyyah in the family vision of Rābi‘ah al-‘Adawiyyah through Syarh ‘Uqud al-Lujain, using a qualitative-descriptive approach and Sufi reflection. The findings highlight two main points. First, the relationship between husband and wife should be built on ukhuwah rūḥaniyyah, or spiritual brotherhood, where each protects the other from harm and strengthens their journey toward salvation in the hereafter. This awareness transforms marital relations into a transcendent bond. Second, the mission and vision of the family should focus on spiritual goals, not merely emotional love. This foundation deepens harmony and may contribute to reducing divorce rates. Thus, Sufi spirituality offers a renewed perspective that the family is not merely a social institution, but a space for soul purification on the path toward a sakinah (serene) household.